The torch bearer of Indian music : Maharshi Vishnu Digambar Paluskar - Ram Avtar (Pankaj Publications : distributors, Cambridge Book & Stationery Stores, 1978)
On Vishnu Digambar Paluskar, 1872-1931, exponent of Hindustani classical music.